Manajemen Resiko Pembiayan Mudharabah Pada Bank Syariah (Studi Kasus Pada Bank Muamalat Indonesia Cabang Banda Aceh) - Lisnawati Lisnawati (Politeknik Kutaraja, 2020)
The purpose of this research was to determine the risk management of mudharabah financng in islamic banking with case study in Bank Muamalat Indonesia cabang Banda Aceh. This analysis is based on consept of mudharabah financing have higher risk than other financing, because there are loss profit sharing consept in islamic banking therefore islamic banking have special management to distribution this financing. The method of the research is using a qualitative approach with field research and case study strategy. The data collection is conducted direcly in Bank Muamalat Indonesia cabang Banda Aceh through interview with marketing manager and account manager of Bank Muamalat Indonesia cabang Banda Aceh. The results of the research showed that to avoid risk of mudharabah financing, Bank Muamalat Indonesia cabang Banda Aceh apply combination contract that is mudharabah wal murabahah contract. Mudharabah financing channeled to cooperative business because more lower risk. There are still obstacles to distribute mudharabah financing to other business